23 Earlier Therapy Intervention in the Emergency Department to Improve Clinical Outcomes for Fallers Aged 65 and Over. (6th February 2020) - Roberts, F
Abstract: Purpose: To improve clinical outcomes for fallers aged 65 and over presenting to the emergency department through earlier therapy intervention and multidisciplinary focussed assessments. The intended benefits to the older person and service were for: Older adult fallers to be referred more quickly for a therapy assessment. Older adults to spend less time immobile on an emergency department trolley. Timely multidisciplinary discharge plans being formulated in line with national guidelines. Increased numbers of older adults receiving holistic comprehensive geriatric assessments. Methods: The quality improvement project was carried out using the Plan, Do, Study, Act (PDSA) cycle. Three iterative PDSA cycles were carried out over the course of the project to deliver simple, proactive interventions developed as a result of local baseline data analysis as well as stakeholder and root cause analysis. These interventions were all aimed at increasing the visual presence of the therapy team within the emergency department. Results: The project resulted in an increased referral speed of fallers aged 65 and over for assessment, which led to increased numbers of older adult fallers receiving holistic, multidisciplinary assessments. 120% more adult fallers were seen in January 2019 compared to the previous year, and 58% more fallers were seen in February 2019 compared to 2018. The earlier intervention by the therapy team also led to more older adults up and moving sooner, which had positive effects in terms of maintaining their dignity. Conclusions: The quality improvement project found that more older adults aged 65 and over admitted to the emergency department with a fall can receive holistic, multidisciplinary assessments through the introduction of small, simple interventions aimed at increasing the proactivity and overall visual presence of the physiotherapy team. The team are providing care to a larger number of older adults, improving their functional independence, dignity and quality of life and giving them an overall more positive experience. The ED model of care is traditionally nursing and medical led but what this improvement project shows it that it is essentially the collaborative nature of the multidisciplinary team that can lead to better clinical outcomes for older adults attending the emergency department.